A Typology of School–Community Relationships: Partnering and Universal Prekindergarten Policy. (July 2016) - Casto, Hope G.; Sipple, John W.; McCabe, Lisa A.
School–community relationships can serve many goals ranging from enhancing student achievement to community development. This article examines the relationship between school–community partnerships and community development in light of a state prekindergarten policy that requires partnering. To understand the local responses, we propose a typology using a continuum of partnering, from isolation to committed partner, and a continuum of community health, from declining to growth. Using mixed-method analysis, we apply this typology to the Universal Prekindergarten policy in New York State. The relationship among these measures illustrates the potential role of state education policy to positively or negatively affect the health of a community.